Analysis of Teaching Methods and Student Perceptions in Learning English Speaking Skills - Rian Muhammad Sofian; Yousef Bani Ahmad (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to identify and analyze the teaching methods employed by lecturers to enhance speaking skills among university students in Karawang. Mastery of speaking skills in a foreign language is crucial for students, not only for academic success but also for professional development in the future. Despite its importance, teaching speaking skills often faces challenges, such as determining the most effective methods to improve students' speaking abilities. This research adopts a qualitative approach using narrative inquiry to explore various teaching methods utilized by lecturers and the perceptions of students towards these methods. Data were collected through interviews and classroom observations involving five randomly selected students who have participated in speaking courses. The findings indicate that teaching methods incorporating active interaction, constructive feedback, and the use of technology significantly enhance students' speaking skills. Students responded positively to more interactive and technology-based methods, which allowed them to practice speaking in contexts closer to real-life situations. The study also revealed that students' confidence in public speaking increased when supported by a positive learning environment and inclusive teaching methods. This research provides valuable insights for educators in developing more effective teaching strategies to improve students' speaking abilities. Therefore, the findings from this study are expected to contribute to the development of better curricula and more innovative teaching programs in higher education.